Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21129/nerve.2018.4.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic C1–C3 Spinal Epidural Hematoma Presented with Occipital Neuralgia

Abstract: A 32-year-old woman presented to our hospital with occipital headache for >1 week following head trauma. She showed no other neurologic symptoms. Pain was aggravated by cervical flexion. Magnetic resonance imaging (MRI) findings showed a spinal epidural hematoma (SEH) at the C1 to C3 level. The C2 roots were encircled and compressed by the hematoma. Medication was prescribed and a neck collar was applied for symptom control. After three weeks, her occipital neuralgia disappeared and cervical flexion did not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Regarding treatment, our review of the literature has shown that the two attitudes are the same, namely a surgical approach [ 11 - 13 ] or conservative treatment [ 9 , 14 , 15 ], associated in all cases with boluses of corticosteroids with analgesic treatment. Staying in ICU depends on the general clinical state of the patient at admission.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding treatment, our review of the literature has shown that the two attitudes are the same, namely a surgical approach [ 11 - 13 ] or conservative treatment [ 9 , 14 , 15 ], associated in all cases with boluses of corticosteroids with analgesic treatment. Staying in ICU depends on the general clinical state of the patient at admission.…”
Section: Discussionmentioning
confidence: 99%